1999
DOI: 10.1111/j.1469-445x.1999.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in pH and PCO2 on Wall Tension in Isolated Rat Intrapulmonary Arteries

Abstract: summaryWe examined mean (± s.e.m.) changes in wall tension in isolated rat intrapulmonary arteries on switching from control conditions (pH 7·38 ± 0·01; PCOµ, 34·4 ± 0·5 mmHg) to hypercapnic acidosis (pH change, −0·24 ± 0·01; PCOµ change, +27·5 ± 0·9 mmHg), isohydric hypercapnia (pH change, −0·02 ± 0·01; PCOµ change, +28·5 ± 0·8 mmHg) and normocapnic acidosis (pH change, −0·24 ± 0·01; PCOµ change, −0·5 ± 0·3). Arteries were submaximally preconstricted with prostaglandin F2á and changes in tension are expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Previous studies of normocapnic acidosis on intact lung or on pulmonary resistance in vivo have produced conflicting results (either a reduction, an increase or no effect on pulmonary vascular resistance -see Sweeney et al, 1999), while systemic vessels typically relax to normocapnic acidosis (rat cerebral artery - Peng et al (1998); rat carotid artery - Sweeney et al, 1999). The membrane potential (in the region of -40 mV in pulmonary arteries) observed in the presence of an acidic extracellular pH was close to the activation threshold of voltage-gated Ca 2 þ channels in arterial myocytes (Clapp & Gurney, 1991 (Peng et al, 1998), little or no change in tone would be anticipated on simply shifting extracellular pH from 7.4 to 6.4 in spite of the ensuing membrane depolarisation.…”
Section: Blood Vessel Tone: Involvement Of Task-1 and Task-2 Channelsmentioning
confidence: 99%
“…Previous studies of normocapnic acidosis on intact lung or on pulmonary resistance in vivo have produced conflicting results (either a reduction, an increase or no effect on pulmonary vascular resistance -see Sweeney et al, 1999), while systemic vessels typically relax to normocapnic acidosis (rat cerebral artery - Peng et al (1998); rat carotid artery - Sweeney et al, 1999). The membrane potential (in the region of -40 mV in pulmonary arteries) observed in the presence of an acidic extracellular pH was close to the activation threshold of voltage-gated Ca 2 þ channels in arterial myocytes (Clapp & Gurney, 1991 (Peng et al, 1998), little or no change in tone would be anticipated on simply shifting extracellular pH from 7.4 to 6.4 in spite of the ensuing membrane depolarisation.…”
Section: Blood Vessel Tone: Involvement Of Task-1 and Task-2 Channelsmentioning
confidence: 99%
“…Sweeney et al (40,41) reported that in the PA, normocapnic acidosis (NA) leads to an endothelium-independent relaxation of isolated PA, which is less than that observed in the aorta. These results suggest that in PA smooth muscle, tension development is relatively resistant to reduction in extracellular pH compared with systemic vascular smooth muscle and that this resistance is an intrinsic property of pulmonary arterial smooth muscle cells (PASMC).…”
mentioning
confidence: 99%
“…This resistance to acidosis plays an important role in ventilation-perfusion matching in the lung in such diseases, since a vasodilator response to hypercapnic acidosis would antagonize hypoxic vasoconstriction in poorly ventilated regions of the lung, thus diverting blood to these regions and impairing normal gas exchange. Sweeney et al (40,41) reported that in the PA, normocapnic acidosis (NA) leads to an endothelium-independent relaxation of isolated PA, which is less than that observed in the aorta. These results suggest that in PA smooth muscle, tension development is relatively resistant to reduction in extracellular pH compared with systemic vascular smooth muscle and that this resistance is an intrinsic property of pulmonary arterial smooth muscle cells (PASMC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 In brief, the rings were mounted on a Mulvaney-Halpern small vessel dual myograph (Model 410A, Linton Instrumentation, Norfolk, England) using two 40 mm intraluminal wires. 25 Isometric tension was recorded as a function of time using an analogue to digital system (Biopac MP100 WS, Linton Instrumentation, Norfolk, England) connected to a desktop computer (Apple Macintosh Performa 6200).…”
Section: Experimental Set-upmentioning
confidence: 99%